Internet Freedom and Digital Journalism in Transitional Contexts: A Comparative Legal–Communication Approach - Ahmed, BOULBARI; Sara, BOUAIFI (Journal of Ecohumanism, 2026)
This study examines the interactive relationship between the legal frameworks regulating internet freedom and the actual practices of digital journalism in transitional contexts, with a focus on the Maghreb region. It adopts an integrative legal–communication approach, employing a comparative method to analyze cases from Algeria, Tunisia, and Morocco. The findings reveal a structural gap between legal texts and real-world application, where ostensibly advanced laws are emptied of their content through indirect censorship mechanisms. The study also highlights the mutual adaptation dynamics between authorities and digital journalism, as well as the increasing role of global digital platforms and their algorithms in shaping the digital public sphere. It proposes a three-dimensional interpretive model (legal, practical, technological) to understand the specificity of transitional contexts, and emphasizes the necessity of moving beyond the mechanical transfer of Western models and building approaches that consider local and regional contexts.